IMPROVING WRITING SKILL OF JUNIOR HIGH SCHOOL STUDENTS THROUGH PICTURE SERIES MEDIA - Oktaviani, Esti Dwi (Universitas Borneo Tarakan, 2019)
This research objective was to find out whether there was any significant difference in students’ writing skill before and after being taught using Picture Series media in learning recount text at Eighth grade students of SMP Negeri 8Tarakan. The design of this research was Pre-Experimental research. The population in this research was all of the eighth grade students at SMP Negeri 8 Tarakan. The sample in this research was 30 students. The sample was chosen by using purposive sampling technique. Class for treatment was VIII-6. It consisted of 30 students. The steps in this research were pretest, treatment, and posttest. In the pretest, the students were asked to write the writing test. After giving the pretest, the researcher gave treatment. The treatment class was taught by using Picture Series media. After giving the treatment, students were asked to write the writing test in posttest. In analyzing the data, the researcher was used paired sample t-test in SPSS 24.0. The result of this research showed that there was different mean score in pretest and posttest. It was proven by the result of the students’ mean score from pretest was 36.27 and 43.20 in the posttest. It means that the improvement of the students’ mean score was 6.93. The result of Paired Sample t-test was 2.119 higher than t-table was 2.045. It means that the students’ writing skill in recount text have an improvement after giving the treatment. The result of sig (2 tailed). 0.000 is lower than 0.05, it means that the Picture Series media can give any contribution to the students’ writing skill. Based on the explanation above, it can be concluded that using Picture Series Media is effective to improve student’s writing skill in recount text.